Transatlantic women travelers, 1688-1843 - Krueger, Misty; Epelbaum, Diana; Johnson, Shelby; Gomashie, Grace; Perkins, Pam; Klein, Ula Lukszo; Golightly, Jennifer; McQuigge, Alexis; Cox, Octavia; Barnett-Woods, Victoria (Transits: Literature, Thought and Culture 1650-1850 Ser., 2021)
This important new collection explores representations of late seventeenth- through mid-nineteenth-century transatlantic women travelers across a range of historical and literary works. While at one time transatlantic studies concentrated predominantly on men's travels, this volume highlights the resilience of women who ventured voluntarily and by force across the Atlantic--some seeking mobility, adventure, knowledge, wealth, and freedom, and others surviving subjugation, capture, and enslavement. The essays gathered here concern themselves with the fictional and the historical, national and geographic location, racial and ethnic identities, and the configuration of the transatlantic world in increasingly taught texts such as The Female American and The Woman of Colour, as well as less familiar material such as Merian's writing on the insects of Surinam and Falconbridge's travels to Sierra Leone. Intersectional in its approach, and with an afterword by Eve Tavor Bannet, this essential collection will prove indispensable as it provides fresh new perspectives on transatlantic texts and women's travel therein across the long eighteenth century.